2022
DOI: 10.1186/s12875-022-01681-3
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, acceptability and costs of nurse-led Alpha-Stim cranial electrostimulation to treat anxiety and depression in university students

Abstract: Background Only a relatively low proportion of university students seek help for anxiety and depression disorders, partly because they dislike current drug and psychological treatment options and would prefer home-based care. The aim of this study is to determine the feasibility, acceptability and cost utility of Alpha-Stim cranial electrostimulation (CES) delivered through a nurse led primary care clinic as a daily treatment for anxiety and depression symptoms by the student at home in contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 26 publications
8
6
0
1
Order By: Relevance
“…The significant improvements in anxiety align with published RCT findings and service based study results (Barclay & Barclay, 2014;Shekelle et al, 2018;Morriss et al, 2019;Griffiths et al, 2021;Royal et al, 2022). This current study's positive remission and reliable improvement rates add to evidence from three other NHS service based Alpha-Stim studies (Morriss et al, 2019;Griffiths et al, 2021;Royal et al, 2022).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The significant improvements in anxiety align with published RCT findings and service based study results (Barclay & Barclay, 2014;Shekelle et al, 2018;Morriss et al, 2019;Griffiths et al, 2021;Royal et al, 2022). This current study's positive remission and reliable improvement rates add to evidence from three other NHS service based Alpha-Stim studies (Morriss et al, 2019;Griffiths et al, 2021;Royal et al, 2022).…”
Section: Discussionsupporting
confidence: 87%
“…Alpha-Stim CES has been delivered through a UK based primary care social prescribing service and evaluation of outcomes found it to be effective in reducing anxiety and depression symptoms and improving health related quality of life; it was found that Alpha-Stim AID was acceptable to most patients, most used as instructed and returned it following use (Griffiths et al, 2021). Delivering Alpha-stim through a nurse led primary care clinic to univer-sity students with a clinical diagnosis of anxiety or depression was found to be acceptable and feasible; improvements in anxiety and depression symptoms were found, and it was calculated to be cheaper than treatment through a general practitioner (GP) (Royal et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Participants found engagement with the Alpha-Stim AID was enabled through the useability of the device, in that it was accessible, easy to use, reliable, could be embedded into their daily routine, and did not have any adverse side effects preventing use; these factors promoted treatment compliance. The findings add to and align with evidence of useability, feasibility, ease of use, and lack of side effects found in other studies (Barclay & Barclay, 2014;Griffiths et al, 2021;Morriss et al, 2019;Royal et al, 2022;Shekelle et al, 2018). Medication side-effects can cause treatment failure (Sundbom & Bingefors, 2013); and the lack of Alpha-Stim AID side effects meant that some participants perceived the Alpha-Stim AID as a preferred alternative to medication.…”
Section: Negative Psychological Effectssupporting
confidence: 83%
“…The participants described reductions in their anxiety and panic attacks, and increases in feelings of calmness and relaxation. This supports evidence from quantitative research, which found Alpha-Stim AID significantly reduces anxiety symptoms (Barclay & Barclay, 2014;Griffiths et al, 2021;Morriss et al, 2019;Royal et al, 2022;Shekelle et al, 2018). Participants reported improvements in sleep quality and duration.…”
Section: Negative Psychological Effectssupporting
confidence: 80%
See 1 more Smart Citation